The Effects of Chicken Manure Fertilizer Application on the Growth and Production of Green Bean Plants (Vigna radiata L.) in Peat - Wiliodorus Wiliodorus (Department of Agribusiness, Halu Oleo University, 2022)
Green bean plants (Vigna radiata L.) are one of the bean plant commodities commonly consumed by Indonesians. The domestic demand for green bean plants is increasing every year. This increasing demand is shown by the fact that there is an increase in the need to satisfy the direct consumption and to meet the need for the supply of industrial raw materials, such as the baby food industry, canned drinks, and processed food. Peatland is a fragile area with a low level of productivity. The low productivity level of peatland is due to the low availability of the macro and micronutrients for plants, the high level of acidity, and the low base saturation. This research aims to identify the exact dose of chicken manure fertilizer to increase the growth and production of green bean plants. The method used to conduct this research was Completely Randomized Design (CRD), with five levels of treatment as a first step to identifying site-specific varieties. Each treatment was repeated on two plant samples: the control, five metric tons/ha, ten metric tons/ha, and 20 metric tons/ha. The application of the chicken manure fertilizer showed positive effects on the improvement of the soil structure, the soil biota, and the availability of the macro and micronutrients, such as nitrogen, phosphorus, and potassium. The application of the chicken manure fertilizer in this research showed the effect on the growth and production of the green bean plants. The application of the chicken manure fertilizer with the amount of 20 metric tons showed the highest results in terms of the height of the plant, the number of leaves, the number of pea pods, and the weight of the pods if compared to the other treatments with different amount of the chicken manure fertilizer.